Порівняльний аналіз блочних симетричних шифрів - Мартиненко, Я. А.; Євгеньєв, А. М. (ХНУРЕ, 2021)
The disclosure of the relevance of this topic in the XXI century. The definition of block ciphers. The description of the main difference from stream symmetric ciphers. The demonstration of the brief description (key length, blocksize, number of rounds, etc.) some of the most important algorithms in US history. The assessment of crypto resistance, using these ciphers as an example. The demonstration of the spreadsheet to compare their characteristics. Based on the analyzed material, the generalization of the most reliable information protection algorithm among 3 ciphers.
Keywords: блочний шифр; DES; AES; розмір блоку